2016
DOI: 10.5935/abc.20160076
|View full text |Cite
|
Sign up to set email alerts
|

Association between Spirituality and Adherence to Management in Outpatients with Heart Failure

Abstract: BackgroundSpirituality may influence how patients cope with their illness.ObjectivesWe assessed whether spirituality may influence adherence to management of outpatients with heart failure.MethodsCross sectional study enrolling consecutive ambulatory heart failure patients in whom adherence to multidisciplinary treatment was evaluated. Patients were assessed for quality of life, depression, religiosity and spirituality utilizing validated questionnaires. Correlations between adherence and psychosocial variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
62
1
7

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(71 citation statements)
references
References 37 publications
1
62
1
7
Order By: Relevance
“…There are studies that suggest the positive influence of spiritual beliefs on health beliefs; those with greater spirituality tend to have greater self-care, deal with illness better, and seek health care more; attributing better health to spiritual strength. [26][27] It is noteworthy that identifying the indicative depression scores helps in the prevention of disease and enables the creation of strategies to care for the symptoms. The increase in the indicative depression score proportionally decreased the QoL scores measured by WHOQOL-BREF in studies with adults and the elderly in China.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies that suggest the positive influence of spiritual beliefs on health beliefs; those with greater spirituality tend to have greater self-care, deal with illness better, and seek health care more; attributing better health to spiritual strength. [26][27] It is noteworthy that identifying the indicative depression scores helps in the prevention of disease and enables the creation of strategies to care for the symptoms. The increase in the indicative depression score proportionally decreased the QoL scores measured by WHOQOL-BREF in studies with adults and the elderly in China.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were included if they (a) were ≥18 years of age, (b) were diagnosed with COPD on the basis of lung function testing (postbronchodilator forced expiratory volume in the first second [FEV1]/forced volume capacity [FVC] <70%), (c) used airway medications for at least one year, (d) had no psychiatric diagnosis and communication problems, and (e) had volunteered to participate in the study. The minimum sample size was calculated using the G Power 3.0 program, based on medium effect size (0.3) with a power of 0.96 and an alpha level of 0.05, and the minimum sample size was determined as 112 COPD patients (Alvarez et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The relationship between spirituality and medication adherence has been investigated in chronic conditions such as chronic heart failure, hypertension, human immunodeficiency virus infection and asthma (Ahmedani, Peterson, Wells, Rand, & Williams, 2013; Alvarez et al, 2016; Dalmida et al, 2017; Kretchy et al, 2013). Studies examining the effects of spirituality in patients with COPD mostly focused on health‐related quality of life and suggested that patients with better spiritual well‐being can manage symptoms properly and have a higher quality of life (Duarte, Lucchetti, Teixeira, & Rigatto, 2018; Hasegawa et al, 2017; Silva, Kimura, Stelmach, & Santos, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Psychological symptoms may have an impact on adherence to treatment in heart failure, as demonstrated in recent studies. 13 …”
Section: Introductionmentioning
confidence: 99%